Preterm Delivery in the Setting of Left Calyceal Rupture - Brent Hanson; Rami Tabbarah (Case Reports in Obstetrics and Gynecology)
Spontaneous rupture of the renal collecting system is a rare but serious complication of pregnancy. We report a case of nontraumatic left renal calyceal rupture in a pregnancy which ultimately progressed to preterm delivery. A 29-year-old primigravida with a remote history of urolithiasis presented with left flank pain, suprapubic pain, and signs of preterm labor at 33 weeks of gestation. The patient was believed to have urolithiasis, although initial renal ultrasound failed to demonstrate definitive calculi. After a temporary improvement in flank pain with medication, the patient experienced acute worsening of her left flank pain. Urology was consulted and further imaging was obtained. Magnetic resonance imaging (MRI) was consistent with bilateral hydronephrosis and rupture of the left renal calyx. Given the patient’s worsening pain in the setting of left calyceal rupture, the urology team planned for placement of a left ureteral stent. However, before the patient could receive her stent, she progressed to active labor and delivered a viable female infant vaginally. Following delivery, the patient’s flank pain resolved rapidly and spontaneously, so no surgical intervention was performed. A summary of the literature and the details of this specific clinical situation are provided.